Glacial discharge along the west Antarctic Peninsula during the Holocene - Pike, Jennifer; Swann, George E.A.; Leng, Melanie J.; Snelling, Andrea M. (Nature Publishing Group, 2013)
The causes for rising temperatures along the Antarctic Peninsula during the late Holocene have been debated, particularly in light of instrumental records of warming over the past decades. Suggested mechanisms range from upwelling of warm deep waters onto the continental shelf in response to variations in the westerly winds, to an influence of El Niño–Southern Oscillation on sea surface temperatures. Here, we present a record of Holocene glacial ice discharge, derived from the oxygen isotope composition of marine diatoms from Palmer Deep along the west Antarctic Peninsula continental margin. We assess atmospheric versus oceanic influences on glacial discharge at this location, using analyses of diatom geochemistry to reconstruct atmospherically forced glacial ice discharge and diatom assemblage ecology to investigate the oceanic environment. We show that two processes of atmospheric forcing—an increasing occurrence of La Niña events and rising levels of summer insolation—had a stronger influence during the late Holocene than oceanic processes driven by southern westerly winds and upwelling of upper Circumpolar Deepwater. Given that the evolution of El Niño–Southern Oscillation under global warming is uncertain, its future impacts on the climatically sensitive system of the Antarctic Peninsula Ice Sheet remain to be established.